Molecular surveillance of artemisinin resistance-linked PFK13 gene polymorphisms in Adamawa State, Nigeria - Mahmoud Suleiman Jada; Yusuf Umar; Aliyu Abdullahi Pela; Auwal Adamu; Hauwa Ahmed Zailani; Abdullahi Usman Wurochekke (Journal of Research in Applied and Basic Medical Sciences, 2025)
Background & aims: The evolution and spread of Plasmodium falciparum malaria parasite capable of evading antimalarials, particularly artemisinin (ART), is a prime concern for malaria control. Mutations in the P. falciparum Kelch 13 (Pfk13) gene confer resistance to artemisinin, necessitating molecular surveillance of Pfk13 mutations. This study is aimed at investigating artemisinin resistance linked Pfk13-propeller polymorphisms in clinical isolates of P. falciparum from three Local Government Areas (Yola North, Numan and Mubi North), of Adamawa State, Nigeria. Materials & methods: A total of 240 symptomatic malaria patients were recruited for this study. Eighty febrile patients diagnosed with uncomplicated P. falciparum malaria attending two major selected healthcare facilities in each of the three Local Government Areas were used. P. falciparum parasite was identified by Rapid Diagnostic Tests (RDTs) and Microscopy. DNA extraction and nested PCR were performed on positive samples to amplify the Pfk13 propeller domain. Sequencing and sequence analysis were conducted to check for mutations at validated codon positions. Results: Out of the 240 samples collected, RDT revealed 100% to be positive for P. falciparum while microscopy confirmed P. falciparum presence in 214 samples (89.17%). Extraction and amplification of Pfk13 gene were successful in 163 samples (67.92%). Out of 163 successfully amplified samples, no validated mutations linked to artemisinin resistance were found, but the A578S mutation was detected in 15.09% of the analyzed samples. Conclusion: The absence of Pfk13 gene mutations indicates the sensitivity of the parasites in this study location to artemisinin treatments, but the mutant A578S observed needs to be investigated to determine its functional relevance in the Pfk13 propeller-domain. However, continuous surveillance and research are crucial to maintain these successes and address any future challenges posed by drug resistance.